Imaging and clinical features of breast tuberculosis: a review series of 62 cases. Issue 7 (July 2020) - Mathew, D.; Rubin, G.; Mahomed, N.; Rayne, S.
Abstract : AIM: To outline the disease burden of breast tuberculosis (TB) as a quantitative analysis amongst three tertiary hospitals in South Africa, with correlation to their clinical, demographic, and imaging features. MATERIALS AND METHODS: A retrospective analysis was undertaken over an 18-month period (01/01/2017–30/06/2018) of all patients undergoing laboratory investigations for breast disease at the mammography departments of these three tertiary centres. RESULTS: The prevalence of breast TB was 2.5% ( n= 62) of 2, 516 patients. The median age of presentation was 38.5 years (interquartile range [IQR] 33–45). HIV status was known in 45 patients, of whom 36 were HIV infected (80%, 95% CI: 0.65–0.90, p< 0.0001). Based on the ultrasound and/or mammogram findings, the patients were classified into five categories: TB breast abscess (40.3%), inflammatory/disseminated (24.2%), isolated TB lymphadenitis (22.6%), nodular (11.3%), and sclerosing form (1.6%). Histology demonstrated necrotising granulomatous inflammation in 57 cases (92%). Acid-fast bacilli (AFB) were positive in 8.1% ( n= 5) of the cytology and 16.1% ( n= 10) of the histology specimens. Culture for Mycobacterium tuberculosis was positive in 27% (17 cases), and in 12.9% ( n= 8). AFB were detected histologically using polymerase chain reaction (PCR) testing. CONCLUSION: Knowledge of the varied clinical and radiological features is necessary to maintain a high degree of suspicion to prevent misdiagnoses, inappropriate management, and complications. Ultrasound-guided core biopsy rather than fine-needle aspiration (FNA) is advocated as the first-line intervention in diagnosing or excluding this disease, as it yields a better tissue sample and more often a positive diagnosis. Highlights: HIV co-infection is a major risk factor for breast TB. High index of suspicion required particularly if immune-compromised or in TB endemic countries. Tissue samples to be sent for TB analysis in non-resolving breast abscesses. Breast TB is a paucibacillary, disease. Histological specimens demonstate necrotizing granulomatous inflammation.